The Improved Amplify-and-Forward (IAF) three time periods TDMA fashioned protocol with inter-relay communication - Imranullah, Khan; Tan, Chong Eng; Baig, I. (Indian Society for Education and Environment, 2015)
The TDMA constructed protocols have been planned (i.e., proposed) by various researchers. These protocols are generally two time periods or three time periods based, and have shown significant reduction in Bit Error Rates (BER), because of low diversity order. Consequently, the Improved Amplify-and-Forward (IAF) protocol has been proposed. The IAF protocol uses three time periods, to transmit data from transmitter to receiver. Moreover, the transmitter is stimulated during the second as well as third time periods, to broadcast to receiver, and the diversity order is improved. It is shown from results that IAF demonstrated significant reduction in BER and rise in BER-Gain, over the previous proposed two time periods as well as three time periods protocols. The IAF protocol demonstrated substantial improvement in Global-Percentage-Error- Decrease (GPED) and Local-Percentage-Error (LPED) values, both at severe as well as at low fading conditions, over to previous proposed TDMA constructed protocols (i.e., two time periods as well as three time periods based).